2020
DOI: 10.1177/1178632920934497
|View full text |Cite
|
Sign up to set email alerts
|

The Privatization of Health Care System in Saudi Arabia

Abstract: Saudi Arabia’s Vision 2030 highlights the development of the health care sector through privatization. This study examines the factors that prompted the privatization of the health care sector in Saudi Arabia. This is a scoping review based on an extensive review of both published and unpublished documents. We have accessed different search engines and databases to collect various research publications, journal articles, government reports, policy and planning documents, and relevant press reports/articles. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 51 publications
1
96
0
Order By: Relevance
“… 19 , 28 , 29 , 30 These studies found that, at the macro-level, the Saudi government chose privatisation as a solution to address the fragmented, financially dependent, unsatisfactory and low-quality health care system. 29 , 30 The overwhelming dependence of the health care system on governmental funding is threatened by an unstable, oil-dependent national economy; thus, the government realised the need to privatise the health care system to reduce government expenditure and provide better health care services, especially with the emergence of new diseases, the growth of the Saudi population and the increase in the population's life expectancy. 21 , 30 , 31 By 2030, the population of KSA will reach 39.3 million, and life expectancy is projected to reach 76.6 years.…”
mentioning
confidence: 99%
“… 19 , 28 , 29 , 30 These studies found that, at the macro-level, the Saudi government chose privatisation as a solution to address the fragmented, financially dependent, unsatisfactory and low-quality health care system. 29 , 30 The overwhelming dependence of the health care system on governmental funding is threatened by an unstable, oil-dependent national economy; thus, the government realised the need to privatise the health care system to reduce government expenditure and provide better health care services, especially with the emergence of new diseases, the growth of the Saudi population and the increase in the population's life expectancy. 21 , 30 , 31 By 2030, the population of KSA will reach 39.3 million, and life expectancy is projected to reach 76.6 years.…”
mentioning
confidence: 99%
“…However, only 3 regions will come under the implementation phase, including the East, Makkah and Riyadh regions, due to higher consumer presence and demand for healthcare in these regions. 37 …”
Section: Resultsmentioning
confidence: 99%
“…The privatization move was aimed at increasing private sector participation in the healthcare sector from 25% to 35% in line with the requirements of Vision 2030, which seeks to provide free and quality healthcare to 20 million Saudi citizens. 37 , 38 The government is undertaking different reform initiatives to boost the healthcare sector. The privatization of the health sector is one of the focal points of government economic diversification activities to minimize public sector expenditures and reduce dependence on it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-communicable diseases (NCDs) now contribute signi cantly to national disease burdens globally [5], and in Saudi Arabia, these account for approximately 73% of total mortality [6,7]. Saudi Arabia has a nationalised healthcare system with government supported care provided through many public health channels with increasing participation of the private sector in recent years [8]. Recently in Saudi Arabia, healthcare reforms within the national transformation program 2020 (part of Vision 2030, 2016) were proposed by the Ministry of Health (MoH) [9].…”
Section: Introductionmentioning
confidence: 99%